2019
DOI: 10.1016/j.thromres.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in pulmonary embolism

Abstract: Sex-specific differences regarding risk factors, symptoms and prognosis have been reported for several cardiovascular diseases. For patients with pulmonary embolism (PE), sex-specific data are limited and inconsistent. We aimed to investigate sex-specific differences in PE. Materials and methods: Over a 10-year period (01/2003-09/2013), patients with confirmed PE were enrolled in a prospective single-centre cohort study. Results: We prospectively examined 569 PE patients (55.9% women). Men more often had cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 47 publications
(76 reference statements)
1
25
2
1
Order By: Relevance
“…Both K s and CLT were associated with positive TnT and NT-proBNP, biomarkers related to the cardiac injury, cardiac stress, and RV dysfunction in acute PE 3 , 22 . Levels of NT-proBNP have been shown to predict the 30-day adverse outcome in acute PE patients 23 . Of note, the 2019 ESC Guidelines for the diagnosis and management of acute PE downplayed the role of NT-proBNP in PE mortality risk estimation 3 , however, it is still considered as an additional prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Both K s and CLT were associated with positive TnT and NT-proBNP, biomarkers related to the cardiac injury, cardiac stress, and RV dysfunction in acute PE 3 , 22 . Levels of NT-proBNP have been shown to predict the 30-day adverse outcome in acute PE patients 23 . Of note, the 2019 ESC Guidelines for the diagnosis and management of acute PE downplayed the role of NT-proBNP in PE mortality risk estimation 3 , however, it is still considered as an additional prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…94,95 Although sex is not a factor in the sPESI, several studies have suggested that it may predict adverse outcomes more accurately in women than men despite that it performs well in both sexes. 57,96 In addition, using sex-specific biomarker cutoff values was shown to improve the performance and predictive value of the 2014 ESC guidelines, though this finding has not been replicated. 57 Future investigations should focus on sex-specific prognostic factors in acute PE.…”
Section: Severity Assessment and Treatmentmentioning
confidence: 96%
“…however, tachycardia and hypoxia reliably predict adverse outcomes in both sexes. 57 Although sex was included in the 2005 PESI score, in the derivation of the simplified PESI score in 2010, it was not found to be a significant predictor of mortality. 91,94 The sPESI score has since been both internally and externally validated in cohorts that were pre-dominantly female (55%-60%).…”
Section: Severity Assessment and Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Although increased incidence of pulmonary embolism in women among both of these age groups may be contributing to this, whether true sex and/or gender differences exist in case fatality rates remains to determined. Data from registry studies have suggested a higher in-hospital and 30 day pulmonary embolism related mortality in women,21 whereas other studies have not observed a difference 22. Subgroup analyses of RCTs comparing warfarin and DOAC therapy have not suggested a difference.…”
Section: Epidemiologymentioning
confidence: 98%